Ipteks Bagi Masyarakat (IBM) Kelompok Nelayan Bagan Perahu Di Kabupaten Kepulauan Selayar - Andi Assir Marimba; Muhammad Kurnia; Najamuddin Najamuddin; Musbir Musbir; Achmar Mallawa (Universitas Hasanuddin, 2020)
“Bagan Perahu” is one of fishing gears that are operated in the waters of Selayar Archipelago District. There are two kinds of “Bagan Perahu” i.e bagan with one boat and with two boats. Bagan with one boat is large than Bagan with two boats. Productivity of two- boat bagan is smaller than that of the one boat bagan, therefore the idea was arose to increase catches of the two-boat bagan by increasing the number of lamps, however those lamps would be mounted on the raft instead of on the Bagan. During operations the light raft would be drifted by currents away from bagan and left it for several hours in order to allow it attracted the fish. Before hauling the net of Bagan light raft would be pulled back to the bagan and after it close enough then the lights would be turned off so that fish which was originally collected by light raft would move to the bagan.In order to be able to test the idea, this Community Service Activity was made by making a light raft and then taught to the communities how to operate it to the “Bagan” in Selayar Islands Regency.